2011
DOI: 10.1590/s0004-28032011000100002
|View full text |Cite
|
Sign up to set email alerts
|

TRREMS procedure (transanal repair of rectocele and rectal mucosectomy with one circular stapler): a prospective multicenter trial

Abstract: Current trial results suggest that TRREMS procedure is a safe and effective technique for the treatment of anorectocele associated with mucosa prolapse. The stapling technique is low-cost as requires the use of a single circular stapler.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Many forms of treatment have been proposed with varying results, including fiber ingestion, laxatives, biofeedback therapy, electrostimulation, sacral nerve stimulation and surgical repair (8,9,12,13,21,23,27) . A total of 175 patients with obstructed defecation syndrome and a Wexner's constipation score ≥6.0 were assessed with 3-D dynamic anorectal ultrasonography (echodefecography) to identify pelvic floor dysfunctions in the posterior compartment (rectocele, intussusception, mucosal prolapse and anismus) and the middle compartment (Grade-III enterocele/sigmoidocele).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many forms of treatment have been proposed with varying results, including fiber ingestion, laxatives, biofeedback therapy, electrostimulation, sacral nerve stimulation and surgical repair (8,9,12,13,21,23,27) . A total of 175 patients with obstructed defecation syndrome and a Wexner's constipation score ≥6.0 were assessed with 3-D dynamic anorectal ultrasonography (echodefecography) to identify pelvic floor dysfunctions in the posterior compartment (rectocele, intussusception, mucosal prolapse and anismus) and the middle compartment (Grade-III enterocele/sigmoidocele).…”
Section: Discussionmentioning
confidence: 99%
“…After excluding patients with slow transit and reduced anal pressure, 23 subjects were submitted to rectocele repair with the TR-REMS procedure (transanal repair of rectocele and rectal mucosectomy with a single circular stapler) which makes it possible to remove the anorectal mucosa circumferentially and reinforce the anterior anorectal junction wall with the use of a single circular stapler and a novel surgical device kit (9) . The few observed complications (2/23; 8.7%) were easily treated during hospitalization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this current issue of ARQUIVOS de GASTROENTEROLOGIA a multicentric study with the use of mechanical suture in rectocele surgical correction is published (2) . The evolution of mechanical sutures by means of stapler use has become a real technological advancement process, as it has represented the concept of a new product with the combination of new functions that have resulted in improvements and effective gains of quality or productivity in the handicraft suture process that has been done by surgeons for centuries, particularly in visceral anastomoses.…”
mentioning
confidence: 99%
“…In colon's resection, staplers had long increased as well as laparoscopic approach, allowing its use in a large number of segments of the anastomoses with linear or circular staplers. Several randomized trials have demonstrated the effectiveness of the PPH (procedure for prolapsed and hemorroidopexy) (9) in the treatment of hemorrhoids (3,7) , and rectal prolapsed, with special attention to the selection of indications (2) .…”
mentioning
confidence: 99%